TIMP way to stop metastasis? - Jarosz, Katarzyna; Chudzik, Robert; Gołębiowska, Maria; Gołębiowska, Beata (Journal of Education, Health and Sport, 2017)
Matrix metalloproteinases (MMPs) are both structural and catalytic proteolytic enzymes. Many MMPs have already been described, each of which is responsible for the distribution and reconstruction of the matrix element. They are the only ones capable of decomposing type IV collagen, which is the skeleton of the basal membrane. They have physiological effects such as scar formation, cyclic endometrial changes, and inflammatory cell migration. Their negative side is the formation of aneurysm, or the enable of tumor infiltration and the formation of distant metastases. They have their own tissue inhibitors of metalloproteinases (TIMPs). The aim of the study is to show to the essence of the issue: acquaintance with current research and development directions as well as threats. Numerous studies point to the huge potential of TIMP and substances regulate expression of MMP and TIMP in the prevention of metastatic disease. Available studies indicate potential use in f. ex. lung cancer, retinoblastoma, bladder cancer, ovarian cancer, and other diseases (cardiovascular, respiratory). Also, it seems possible to use them as a diagnostic marker. However, due to their lack of specificity and wide range of activity, may have many sides effects. More research is needed to look for TIMPs that specifically target specific MMPs.